Os deslocamentos afro-brasileiros em Marcelino Freire - Farias, Cássio Augusto Nascimento (2019)
This paper aims to analyze the mobility and the immobility of the Afro-Brazilian characters in the short stories by Marcelino Freire. As the object of study, we selected seventeen narratives of the writer from Pernambuco that approach the displacement or the desire of displacement of the Afrodescendent characters. Namely: “Uma história de amor que rolou”, from AcRústico (1995); “Troca de alianças”, from Angu de sangue (2005); “Esquece”, “Alemães vão à guerra”, “Vaniclélia”, “Nação zumbi”, “Caderno de turismo”, “Curso superior”, “Meu negro de estimação”, “Solar dos príncipes” and “Polícia e ladrão”, from Contos negreiros (2014); “Roupa suja”, from Rasif: mar que arrebenta (2014); “Vestido longo” and “Modelo de vida”, from Amar é crime (2015); “Ensaio sobre a dança”, “Ensaio sobre a educação” and “Ensaio sobre a educação”, from Bagageiro (2018). From such literary works, we intend to discover how the black identities that succeed or do not succeed to transit around hegemonic territories are represented. We adopted as the methodological basis the inderdisciplinarity proposed by the the Cultural Studies. Initially, we talk about the author from Pernambuco, making a summary of the critical essays concerning his works, in an attempt to outline a poetic of displacement. Therefore, we seek as a foundation the reflections of authors like Vasconcelos (2007), Teles (2017), Silva (2018), Rocha (2015), Souza (2012), Santana (2016), Walty (2005), Conde (2010), Leite (2016), Duarte and Fonseca (2011) and Fiorin (2005). Next, we discuss about the interdependency that unifies space, power and identity. It serves as theoretical contribution the debates of Brandão (2013), Santos (2012, 2014), Gomes (2011), Said (1990, 2011), Woordward (2010), Hall (1994, 2005, 2009) and Ribeiro (2017). Then, we try to contextualize the way that the centre and the periphery are comprehended in the contemporaneity with the help of Deleuze and Guattari (1997), Santos (2008), DaMatta (1979), Bauman (2001, 1999, 2004), Cruz (2015), Carril (2006), Diniz and Cardoso (2015) and Valladares (2005). In the next chapter, through the reflections of authors like Fernandes (2007), Almeida (2018), Souza (2018), Ianni (2004), Munanga (1996), Gonzalez (2017), Carneiro (2011), Marcondes et al. (2013), Bem (2005) and Santos (2002), we comment about the paradoxes that involves the spatial and socioeconomic fixity and mobility of the Afro-Brazilian characters on Marcelino Freire, keeping in mind the globalization and its effects.